Interventions to support Choosing Wisely for coagulation studies in the emergency department. (15th September 2020) - Kalsi, Mandeep S; Foo, Chuan Tai; Farzanehfar, Parisa; Ayoub, Sandy; Tacey, Mark; Pearson, Kristen
Abstract: Objective: To evaluate the effectiveness of two different strategies designed to facilitate implementation of Choosing Wisely Australia guidelines, aiming to reduce unnecessary coagulation study blood tests in patients presenting to a metropolitan hospital ED. Method: In this real‐world quality improvement study, the first intervention tested was an education strategy. The second intervention was physically removing coagulation pathology tubes from the bedside trolleys in the ED. Data were collected about clinical appropriateness of testing, as per the Choosing Wisely Australia guideline and total volume of coagulation studies ordered. Results: No reduction in inappropriate coagulation testing was observed following the education intervention whereas a significant reduction in inappropriate coagulation testing was seen after the second intervention (inappropriate testing reduced from 73.8% to 53.0%). Conclusion: Physically removing coagulation pathology tubes from the trolleys was found to be effective at reducing unnecessary testing. Abstract : A real‐world quality improvement study assessing the effectiveness of two different interventions at reducing unnecessary coagulation study blood tests in patients presenting to a metropolitan hospital ED